RF14 Changes in trajectories for blood pressure among chinese children and adolescents: evidence from china health and nutrition survey 1991–2011. (3rd September 2019) - Gao, M; Wells, J; Li, L
Abstract : Background: High blood pressure (BP) in adults is an important risk factor for cardiovascular disease (CVD) development and mortality. Childhood BP is not affected by antihypertension treatment, tracks into adulthood and is associated with early target organ disease. Previous reviews reported the varied trend of childhood BP between and within countries. Little is known whether BP trajectories during childhood have changed over time in developing countries with rapid economic development like China. As BP is strongly associated with body-size, we investigated whether BP trajectories have changed among Chinese children and adolescents and estimated the role of BMI and height trends to explain the change in BP trajectories during the past 2 decades. Methods: China Health and Nutrition Survey (CHNS), a mixed longitudinal household survey with eight waves from 1991 to 2011, was used to create four birth cohorts (children aged 7–17y, born in 1981–85, 1986–90, 1991–95, 1996–2000, N=∼16000). Within each gender group, mixed effects cubic growth models were applied to estimate child-to-adolescent trajectories for systolic and diastolic BP (SBP and DBP) with and without adjustment for BMI and height by gender- and age-standardised z-scores. Between-cohort differences were examined by testing the interactions of each cohort with age terms. Results: Trajectories for SBP increased across cohorts: those for later-born cohorts tended to lay above early-born cohorts in both genders. After the adjustment of height and BMI, the differences in mean SBP reduced. The reduction was more evident in adolescence (vs childhood) and with adjustment for height (vs for BMI) trajectories. For example, the difference between the last (born in 1996–2000) and first (born in 1981–85) cohorts was 1.90 mmHg ( 95% CI : 0.54–3.26) for boys and 2.58 mmHg ( 95% CI : 1.18–3.98) for girls at 7y, and there was no difference at 16y after adjustments. Similar patterns were seen for DBP. Conclusion: Our study is the first to investigate the change in BP trajectories during childhood in China. Later-born Chinese children and adolescents are characterized by higher BP than the earlier generations at the same age. This BP trend during recent decades was partly explained by more rapid growth in height and BMI in later-born children. Future study should exam other potential risk factors on BP trend in Chinese children.